МІКРОБІОЛОГІЧНІ ПРОЦЕСИ У КОРЕНЕВІЙ ЗОНІ РОСЛИН ГОРОХУ І ПШЕНИЦІ ОЗИМОЇ ЗА ВИРОЩУВАННЯ ЇХ У МОНОКУЛЬТУРІ ТА ЧОТИРИПІЛЬНІЙ СІВОЗМІНІ - Малиновська , І.М.; Літвінов , Д.В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2012)
The peculiarities of various microbiological processes at cultivation of winter wheat and pea crops in the permanent and short crop rotations were studied in stationary experiments. It was established that the cultivation of wheat in a monoculture results in intensification of consumption of soil organic matter as compared to the crop rotations: without applications mineral fertilizers on 52,2 %, with mineral fertilizers – on 77,8 %; increase of humus mineralization: without fertilizer on 111 %, with fertilizer (N60P60K60) – on 15 %; and activation of mineralization of nitrogen compounds on 100 and 60,0 %, respectively. Cultivation of peas in a monoculture was also accompanied by intensification of soil organic matter development: without the application of mineral fertilizers by 3,17 times, with mineral fertilizers – by 1,79 times; increase of humus mineralization by 1,73 and 1,88 times, respectively; and activation of mineralization of nitrogen compounds by 2,38 and 1,88 times, respectively. The decrease of humus mineralization activity in the root zone of pea plants as comparing to the wheat was at 45,7 % (monoculture), 19,2 % (crop rotation) and 46,9 % (crop rotation, NPK) levels.